Mechanical efficiency and skiing speed during roller skiing with diagonal stride techniques - Nakai, A.; Ito, A. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
The purpose of this study was to clarify how mechanical efficiency during submaximal level roller skiing with diagonal techniques (ME) changes with speed. ME was calculated with the total work rate which contained the work for body segment motions and for external loads, and also the energy expenditure rate measured under experimental conditions. Eight male intercollegiate cross-country skiers were roller skied with a diagonal stride at given speeds on an all-weather level track to videotape motions and measure oxygen uptake. The work rate which was supposed all mechanical energies could be transferred within and between all body segments and was summed increase in the whole body energy levels, and the work rate for overcoming frictional loads on roller skis were calculated. Then, both work rates normalized for body mass were summed. This total work rate was divided by the energy expenditure rate which was subtracted energy cost in a resting state, and thus ME was calculated. The results could be summarized as follows. ME increased remarkably with speed up to 3.6 m/s at which ME indicated the maximal value of 0.357, and subsequently shifted to a moderate decrease. This variation of ME could be attributed to reutilization of elastic energy stored in actively stretched muscle-tendon complexes and variation of recruitment patterns of muscle fibers with roller skiing speed. At low speed, less elastic energy could be restored and reused due to small force application and long coupling time in activated muscles, and therefore ME was lower. ME could have a significant increase at middle speed since slow-twitch (ST) fibers, which are efficient in low-intensity exercises, were recruited adequately, and stored elastic energies were reutilized efficiently during stretch-shortening cycles and hence energy expenditure was reduced. At more than middle speed, ST fibers, which deteriorated efficiency in high-intensity exercises, were recruited sequentially, and in addition recruitment of fast-twitch fibers, which were originally more inefficient than ST fibers, was started. These might cause augmentation of energy expenditure and modest degradation of ME consequently. Furthermore, it was suggested that ME during races could be almost as high as its maximal value.